Memórias e histórias de professores e estudantes da Escola Estadual de Uberlândia, Uberlândia - MG - Silva, Janaina Ferreira (2016)
This research addresses experiences and memories of teachers and students of the Escola Estadual de Uberlandia / MG. The delimitation of the study is from 1954 to 2011. I tried to deal with a public educational institution through the histories of its main social subjects, seeking to achieve a relationship between the school and the sense of being a student and professor there. The focus of the problem was the multiplicity of meanings produced by teachers and students within the relationships in that social space of the city of Uberlandia- MG. Analyze the relationship between memories around this public school, which exists in the city for more than eighty years. Among the many memories that teachers and students brought through the interviews was noticeable that there is a dominant memory, which also justifies the fact that the school has become municipal heritage of Uberlandia. The use of oral interviews with teachers and former students pointed to a conflict between diversity memories of this school. This survey also addressed some social trajectories of former student-city workers and school, showing the significance of the study, and still lived process of changes in Brazilian education during the military dictatorship. The work also dealt with the school process being made while a social law, which became more evident during the 1980s, at which teachers will print another sense that we call dominant memory.